2020
DOI: 10.1097/jom.0000000000001992
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Telework and Presenteeism Across Europe

Abstract: Objective: Flexible work arrangements such as telework are gaining importance. Although telework is accompanied by advantages for employees such as increased flexibility, current research reveals associations between home-based telework and self-endangering behavior such as sickness presenteeism. As empirical evidence is still scarce, we explore the relationship between home-based telework and sickness presenteeism across Europe. Methods: We perform multilevel analyses incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 26 publications
2
85
2
4
Order By: Relevance
“…Our results show that residence, marital status, job position, and employment status all influenced the choice of the work method. In contrast to Zhang et al [18], our study shows that married people are more likely to work remotely and that sex has no effect on the choice of telework.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results show that residence, marital status, job position, and employment status all influenced the choice of the work method. In contrast to Zhang et al [18], our study shows that married people are more likely to work remotely and that sex has no effect on the choice of telework.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies by Kitou et al [16] and O'Brien et al [17] have shown that teleworking offsets the beneficial effects of reduced commuting by working longer hours at home, increasing energy use, and transportation. Zhang et al [18] analyzed telework from the perspective of work-life conflict and showed that the association between life dimensions (sex, marital status, and parenthood) and telework behavior is complex. Children play a crucial role in telework performance, by the Ethics Committee.…”
Section: Disadvantages Of Teleworkmentioning
confidence: 99%
“…Although information technology, which assists remote work has remarkably advanced in recent years and it is slightly hard to apply in this circumstance directly, there are some previous reports in the literature that assessed the effects of remote work on mental health, work productivity, and presenteeism, but the conclusions were inconsistent (Di Martino and Wirth, 1990 ; Bailey and Kurland, 2002 ; Martin and MacDonnell, 2012 ; Baert et al, 2020 ; Steidelmüller et al, 2020 ). This inconsistency may be a result of the lack of consideration of confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, remote work can result in social isolation and marginalization, which increases the stress of workers (Di Martino and Wirth, 1990 ), and a literature review reported that there was little clear evidence that remote work increases job satisfaction and productivity (Bailey and Kurland, 2002 ). Moreover, a research group in Europe also concluded that working from home was associated with work productivity loss caused by sickness (Steidelmüller et al, 2020 ), which is also known as presenteeism (Aronsson et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of properly designed desks and chairs can affect the health of workers with musculoskeletal disorders and chronic pain, important problems that cause sickness presenteeism (21,22). Further, a study has suggested that removing barriers to work, such as commuting and going to the office, is also associated with the occurrence of sickness presenteeism (23). Improving workers’ work environment while working from home is important for reducing the negative health outcomes associated with working from home, improving presenteeism, and increasing productivity.…”
Section: Discussionmentioning
confidence: 99%